The Future of L-Arginine Dietary Supplementation Research - The Impact on NOS Dependent and Independent Systems - Gabriels, Gary (British Journal of Healthcare and Medical Research, 2022)
Introduction: The consumption of L-arginine is of particular concern, due to the importance of dietary supplements in people’s daily life, continually increasing. Also, the counter position is the impact of adulterants, contaminants and undeclared constituents in L-arginine products, and consequently to health/wellness. Aim: To contextualize and provide new perspectives for L-arginine dietary supplement research, that would have an impact on the consumers, and patients, health/wellness. Method: The approach was to do a literature search in multiple online electronic academic open-source scientific databases. These covered, PubMed, Scopus, Google Scholar, Elsevier, Taylor & Francis, Sabinet, ScienceDirect, ClinicalTrials.gov, and The Cochrane Collaboration. The search terms covered L-arginine, and the specific research related interest. Outcome: The role of L-arginine in inhibition and control of disease is essentially via the dependent or independent NO metabolic pathways. In L-arginine deficiency, the selective delivery is exogenously taking the amino acid. That there is an impact of dietary arginine containing supplements consumption (or in combination) on human performance (exercise), including effects on cognitive flexibility, and/or mental ability. That L-arginine supplementation is indicated for stress reduction, anxiety, and adaptogenic capabilities in the healthy. However, L-arginine is not lacking, in side effects, including drug-interactions when taken in combination. Gastrointestinal disturbances being the most common adverse effects. Conclusion: Of prominence is the potential benefit, pure L-arginine holds for the consumer. It is recommended that further scientific research scrutiny is warranted. This will provide awareness for an improved specific national regulatory framework, globally, but also set the tone for future research studies.